2022
DOI: 10.1029/2021gc010042
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dras‐Kohistan‐Ladakh Arc Revealed by Volcaniclastic Records

Abstract: Table S4. Whole-rock geochemical compositions of the Jurutze and Nindam formations (Zanskar Gorge, Ladakh, India). File S1. Compilation of references used for comparison in detrital zircon and whole-rock geochemical plots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 172 publications
(283 reference statements)
1
8
0
Order By: Relevance
“…Andjić et al. (2022) argued that a single Dras‐Kohistan‐Ladakh arc formed above a south‐dipping intraoceanic subduction zone and accreted to Eurasia during the Early Cretaceous, after which it evolved above a north‐dipping subduction zone. Based on global tectonic reconstructions and seismic tomography, Yan et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Andjić et al. (2022) argued that a single Dras‐Kohistan‐Ladakh arc formed above a south‐dipping intraoceanic subduction zone and accreted to Eurasia during the Early Cretaceous, after which it evolved above a north‐dipping subduction zone. Based on global tectonic reconstructions and seismic tomography, Yan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Following the Borneo block colliding with the Sundaland margin, the subduction polarity reversed from south-to north-directed at the Woyla Arc. Andjić et al (2022) argued that a single Dras-Kohistan-Ladakh arc formed above a south-dipping intraoceanic subduction zone and accreted to Eurasia during the Early Cretaceous, after which it evolved above a north-dipping subduction zone. Based on global tectonic reconstructions and seismic tomography, Yan et al (2023) reported that a south-dipping intraoceanic subduction system within the Neo-Tethys allowed reasonable geological reconstructions during the Jurassic-Cretaceous period.…”
Section: Large-scale Intraoceanic Subduction System Across the Neo-te...mentioning
confidence: 99%
“…However, we propose that the gabbroic rocks of Nidar, Chilas, and Kargil were formed along the parallel oceanic arc system within the Neo‐Tethys. More recently Andjić et al (2022) advocated a single Dras‐Kohistan‐Ladakh arc based on volcaniclastic records. Considering the comparable whole‐rock geochemical data, it can be deduced that the Cretaceous oceanic island arc system was geographically much more extensive within the Neo‐Tethys, spreading further east to Ladakh.…”
Section: Discussionmentioning
confidence: 99%
“…The younger mafic dykes trending NW-SE in the Tirit granitoids may be related to the activity on the strike-slip Karakoram fault. Evaluating the complex and competing versions of this history, however, requires a more detailed (and expanded) study (Andjić et al 2022).…”
Section: Tectonic Significancementioning
confidence: 99%
“…Evaluating the complex and competing versions of this history, however, requires a more detailed (and expanded) study (Andjić et al . 2022).…”
Section: Tectonic Significancementioning
confidence: 99%